Neglected tropic diseases: a reflexion in times of pandemic about how to intervene under the optics of one health - Wilmer E. Villamil -Gomez (Asociación Colombiana de Infectología, 2023)
On 31 May 2021, the Health Assembly, by its decision WHA74, recognized 30 January as World Day for Neglected Tropical Diseases (NTDs) as a day dedicated to the better diffusion of the devastating impact of these diseases on the poorest po-pulations in the world. NTDs are a heterogeneous group of 20 diseases, prevalent mainly in tropical areas, affecting more than one billion people from impoverished communities1. NTDs are called "neglected" because they have been erased from more developed societies, while they have persisted in the poorest and most marginalized. If left untreated, they can cause illness, suffering, disability and stigma, preventing children from attending school and hindering adult productivity2